Results of 43 lumbar sympathectomy - Castro Suárez, Danilo; Balboa, Oscar; Tchekmedyian, Vartan; Pittamiglio, Horacio; Matteucci, Pablo; Girardi, Gino; Ardao, Gonzalo; Figueredo, Miguel (Cirugía del Uruguay, 1983)
Retrospective analisys of 43 lumbar simpaticectomy, performed in the H. de C. between 1973 and 1981 is performed. lts results with preoperatory arteriography are compared. The best results of this procedure were seen when preoperatory arteriography showed segmenta! lesion of middle and distal sector, with profundis femoralis undamaged.